2019
DOI: 10.3390/ijerph16132318
|View full text |Cite
|
Sign up to set email alerts
|

Urban Road Network Expansion and Its Driving Variables: A Case Study of Nanjing City

Abstract: Developing countries such as China are undergoing rapid urban expansion and land use change. Urban expansion regulation has been a significant research topic recently, especially in Eastern China, with a high urbanization level. Among others, roads are an important spatial determinant of urban expansion and have significant influences on human activities, the environment, and socioeconomic development. Understanding the urban road network expansion pattern and its corresponding social and environmental effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…Previous studies even identified a negative relation between tertiary industry development and urban expansion generally [15,41], while a positive correlation was found in the Pearl River Delta region. Because the development level of tertiary industry in the Pearl River Delta region is high and urban development is significantly driven by tertiary industry [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies even identified a negative relation between tertiary industry development and urban expansion generally [15,41], while a positive correlation was found in the Pearl River Delta region. Because the development level of tertiary industry in the Pearl River Delta region is high and urban development is significantly driven by tertiary industry [36].…”
Section: Discussionmentioning
confidence: 99%
“…Public financial expenditure relates to a government’s investment in public goods and services, such as affordable housing, transportation systems, and public service facilities [29]. Road construction improves accessibility, thus attracting investment and guiding urban expansion [15,16,36]. Therefore, total public finance expenditure (PFX) and change of area of paved roads in cities (ROD) were selected to represent decentralization.…”
Section: Methodsmentioning
confidence: 99%
“…This city is one of the megacities in the Yangtze River basin and has experienced rapid economic development since the 1970s that is still occurring today [29]. At the end of the 20th century, the urbanization of Nanjing entered an accelerated phase, which led to the rapid increase in population, unreasonable industrial structure, unbalanced land use, high energy consumption, and environmental degradation [30,31]. Over the last two decades, the population has increased from 3 M to 8.5 M, and its GDP has increased from 338.12 billion CNY in 2008 to 1171.51 billion CNY in 2018.…”
Section: Study Areamentioning
confidence: 99%
“…Along the rural-urban gradient the number and the density of human inhabitants increases (Montalvo et al, 2019). The urbanization rate is associated with an increase in road density (Shi et al, 2019), area with artificial cover and paved surfaces (Murata & Kawai, 2018;Chen et al, 2020), and air and soil pollution (Duh et al, 2008;Jia et al, 2018). Urban forests are constantly exposed to elevated temperatures, carbon dioxide, nitrogen deposition and ozone (Carreiro & Tripler, 2005).…”
Section: Introductionmentioning
confidence: 99%